ANALISIS TINDAK TUTUR DIREKTIF DALAM DIALOG ACARA MATA NAJWA “KENAPA PERLU KULIAH ALA MAUDY, ANDHIKA, DAN AMANDA” - Apriliani, Risma Sri; Djumingin, Sulastriningsih; Syamsudduha, Syamsudduha (Universitas Negeri Makassar, 2024)
This research is a descriptive qualitative research that aims to (1) Describe the form of directive speech acts in Mata Najwa's Dialogue Show “Why Do I Need to Study ala Maudy, Andhika, and Amanda”. (2) To describe the function of directive speech acts in Mata Najwa's Dialogue Show “Why Do I Need to Go to College ala Maudy, Andhika, and Amanda”. The data in this study are transcripts of speech or fragments of conversations in the video of Mata Najwa Show “Why Do I Need to Go to College ala Maudy, Andhika, and Amanda”. The source of the data is the dialog conversation contained in Mata Najwa Show “Why Do I Need to Go to College ala Maudy, Andhika, and Amanda”. Data collection is done by listening technique, data transcription and note taking technique. Data analysis is done by reducing data, presenting data, and drawing conclusions. From the analysis, it is found that there are six forms of directive speech acts, namely: requests, questions, orders, prohibitions, giving permission, and advice.